Plasma Periostin Levels Are Increased in Chinese Subjects with Obesity and Type 2 Diabetes and Are Positively Correlated with Glucose and Lipid Parameters - Yuanyuan Luo; Hua Qu; Hang Wang; Huili Wei; Jing Wu; Yang Duan; Dan Liu; Huacong Deng (Mediators of Inflammation)
The purpose of this study is to examine the relations among plasma periostin, glucose and lipid metabolism, insulin resistance and inflammation in Chinese patients with obesity (OB), and type 2 diabetes mellitus (T2DM). Plasma periostin levels in the T2DM group were significantly higher than the NGT group (P<0.01). Patients with both OB and T2DM had the highest periostin levels. Correlation analysis showed that plasma periostin levels were positively correlated with weight, waist circumference (WC), body mass index (BMI), waist-hip ratio (WHR), fasting plasma glucose (FPG), 2 h postchallenge plasma glucose (2 h PG), glycated hemoglobin (HbA1c), triglyceride (TG), total cholesterol (TC), fasting insulin (FINS), homeostasis model assessment of insulin resistance (HOMA-IR), TNF-α, and IL-6 (P<0.05 or 0.001) and negatively correlated with high-density lipoprotein cholesterol (HDL-C) (P<0.001). Multiple linear regression analysis showed that TG, TNF-α, and HOMA-IR were independent related factors in influencing the levels of plasma periostin (P<0.001). These results suggested that Chinese patients with obesity and T2DM had significantly higher plasma periostin levels. Plasma periostin levels were strongly associated with plasma TG, chronic inflammation, and insulin resistance.